Severe Impairment in Early Host Defense against Candida albicans in Mice Deficient in Myeloperoxidase - Aratani, Yasuaki (American Society for Microbiology, 1999)
Myeloperoxidase (MPO) catalyzes the reaction of hydrogen peroxide with chloride ion to produce hypochlorous acid (HOCl), which is used for microbial killing by phagocytic cells. Despite the important role of MPO in host defense, however, MPO deficiency is relatively common in humans, and most of these individuals are in good health. To define the in vivo role of MPO, we have generated by gene targeting mice having no MPO activity in their neutrophils and monocytes. The mice without MPO developed normally, were fertile, and showed normal clearance of intraperitoneal Staphylococcus aureus. However, they showed increased susceptibility to pneumonia and death following intratracheal infection with Candida albicans. Furthermore, the lack of MPO significantly enhanced the dissemination of intraperitoneally injected C. albicans into various organs during the first 7 days. Thus, MPO is important for early host defense against fungal infection, and the inability to generate HOCl cannot be compensated for by other oxygen-dependent systems in vivo in mice. The mutant mice serve as a model for studying pulmonary and systemic candidiasis.